2006
DOI: 10.1210/jc.2005-1663
|View full text |Cite
|
Sign up to set email alerts
|

High Serum Levels of Growth Hormone (GH) and Insulin-Like Growth Factor-I (IGF-I) during High-Dose GH Treatment in Short Children Born Small for Gestational Age

Abstract: Our study shows that high-dose GH treatment in short SGA children results in high serum GH and IGF-I levels in most children. We recommend monitoring IGF-I levels during GH therapy to ensure that these remain within the normal range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 37 publications
(53 reference statements)
2
28
0
Order By: Relevance
“…During combined treatment, mean and maximum GH levels were lower in our study group compared with levels in prepubertal SGA children treated with GH only (38). Moreover, maximum GH levels in children treated with GnRHa and 2 mg GH/m 2 per day were similar to maximum GH levels in prepubertal children treated with 1 mg GH/m 2 per day.…”
Section: Start Of Gnrha Treatment (Nz41)supporting
confidence: 46%
See 1 more Smart Citation
“…During combined treatment, mean and maximum GH levels were lower in our study group compared with levels in prepubertal SGA children treated with GH only (38). Moreover, maximum GH levels in children treated with GnRHa and 2 mg GH/m 2 per day were similar to maximum GH levels in prepubertal children treated with 1 mg GH/m 2 per day.…”
Section: Start Of Gnrha Treatment (Nz41)supporting
confidence: 46%
“…GH and IGF1 levels increased significantly in both GH dosage groups, but to significantly higher levels in the 2 mg GH/m 2 per day group. Dose-dependent rises have been described in prepubertal short children born SGA, GH-deficient adolescents, and girls with Turner syndrome (38,43,44). The percentage of children with IGF1 SDS above 2 SDS was not significantly different between the groups.…”
Section: Start Of Gnrha Treatment (Nz41)mentioning
confidence: 93%
“…In recent years, SGA children have been treated with recombinant human GH, and some of them needed an increased GH dose for their poor response. van Dijk M. et al reported children with higher GH and IGF-I levels in combination with a poorer growth response, who may have had IGF-IR gene anomalies [28]. Further studies investigating the possibility and frequency of IGF-IR mutations among familial short-stature, SGA children are desired.…”
Section: Prevalence Of Igf-ir Gene Anomaly In Short-stature Individualsmentioning
confidence: 99%
“…Two children had the same mother but different fathers. Inclusion criteria for the children have previously been described (16). In short, the children were included when prepubertal, with a birth length or birth weight SD score (SDS) and actual height SDS below Ϫ2, without signs of catch-up growth in height and without growth failure caused by other disorders.…”
Section: Methodsmentioning
confidence: 99%